Predators override rainfall effects on tropical food webs. (25th May 2021) - Ospina‐Bautista, Fabiola; Srivastava, Diane S.; González, Angélica L.; Sparks, Jed P.; Realpe, Emilio
Abstract: Predators alter ecological communities by inducing changes in prey abundance and phenotypes, including elemental and isotopic composition. Climatic factors are known to often moderate predator effects on prey abundance, but few studies consider the combined effects of climate and predators on prey phenotype. We examined how altered precipitation moderates the effects of predators on the abundance and the chemical composition of prey, as well as the indirect effects on the basal resource: leaf litter coated in biofilm. Using an experiment with an invertebrate food web module from tank bromeliads, we manipulated the presence of an odonate predator under scenarios of 10‐fold decreased, ambient, and threefold increased precipitation and measured responses of prey and their basal resource. Predators reduced prey abundance while precipitation did not. Both precipitation and predators, either singly or interactively, affected the elemental composition of prey. Predators increased C:N ratios of detritivorous beetles under high precipitation, but reduced the C:N ratio of the basal resource. Precipitation reduced the N content of filter‐feeding mosquitoes. The observed changes in chemical composition may reflect physiological or developmental responses to stress imposed by both predators and drought. This study demonstrates that the impact of predators and precipitation can vary substantially across a food web, including additive and synergistic effects, and numerical and phenotypic responses. Abstract in Spanish is available with online material. Abstract : We designed a field experiment to test the hypothesis that altered rainfall patterns and odonate predator presence affect abundance and elemental composition of invertebrate prey ( Culex sp. and Scirtes sp.) and basal resource within bromeliad food webs. We found that predators, but not precipitation, affected prey abundance. However, predators and precipitation, both alone and in combination, affected various aspects of the elemental content of surviving insect prey and remaining leaf litter. Our results suggest that the impact of predators and rainfall can vary substantially across a food web, including additive and synergistic effects and numerical and phenotypic responses. Resumen: Los depredadores afectan las comunidades ecologicas a través de cambios en la abundancia y fenotipo de las pesas, incluyendo la composición de elementos e isotopica. Se sabe que las variables climaticas regulan el efecto del depredador sobre la abundancia de las presas, pero pocos estudios han considerado el efecto combinado del clima y la depredación sobre el fenotipo de las presas. Se evaluó cómo cambios en la precipitación regulan los efectos del depredador sobre la abundancia y composición química de las presas, así como los efectos indirectos sobre el recurso base, la biopelícula de la hojarasca. Se realizó un experimento utilizando la red trófica de invertebrados de las bromelias tanque, se manipuló la presencia de un depredador odonato bajo los escenarios de disminución de 10 veces la precipitación, ambiental e incremento de 3 veces la precipitación y se midió la respuesta de las presas y el recurso base. El depredador pero no la precipitación redujó la abundancia de las presas; ambos, la precipitación y el depreddor, solo o en interacción afectaron la composición química de las presas. El depredador incrementó la relación C:N de los coleópteros detritivos bajo el tratamiento de precipitación alta pero redujó la relación C:N del recurso base. La precipitación redujo el contenido de N de los mosquitos. Los cambios observados en la composición quimica pueden reflejar las respuestas fisiológicas y de desarrollo al estrés impuesto por el depredador y la sequía. Este estudio demostró que el impacto del depredador y la precipitación pueden variar sustancialmente a través de la red trofica incluyendo efetos aditivos y sinérgicos y respuestas numéricas y fenotipicas.